UJI APLIKASI BERBAGAI TINGKAT DOSIS PUPUK ZA TERHADAP PRODUKTIVITAS DAN MUTU JAGUNG - Fahdiana Tabri; M. Aqil; Roy Efendi (Universitas Negeri Makassar, 2018)
This study aims to see the effect of optimal dosage of ZA fertilizer on maize productivity and quality. The results showed that the treatment without urea, in the treatment of NPK 300 / kg + ZA 100 kg / ha fertilizer dosage will decrease the yield from 10.8 tons / ha to 9.1 tons / ha, and BC Ratio 2.34 to 2, 08. Further treatment without urea (NPK + Urea) has the highest production of NPK fertilizer 300 kg / ha + ZA 200 kg / ha with profit rate Rp. 20.435.000, - and B-C Ratio 2.21. Furthermore the addition of ZA fertilizer doses will actually reduce the production and B-C Ratio